Ultrasound examination of pregnancy in the domestic goat (Capra hircus) ‒ a review - Natalia Wojtasiak (Polish Society of Animal Production, 2020)
Ultrasonography (USG) for embryo-foetal foetometry is widely used in the management of goat breeding. Tissues and organs of the embryo/foetus are measured and evaluated to assess gestational age. Transrectal, transabdominal and transvaginal probes are used to perform the ultrasound examination. Technological advances, especially with regard to ultrasound image resolution, enable precise visualization of embryo-foetal structures in goats. The article reviews the foetometric measurements used in ultrasound examination of pregnancy in goats. Performing this examination during specific periods of gestation enables effective monitoring of embryonic and foetal growth and development. In addition to measurements of embryo-foetal structures, measurements of foetal-maternal structures such as the placentomes and umbilical cord are important as well. The role of ultrasound in monitoring goat pregnancy, both normal and pathological, was also emphasized.